THE ROLE OF SOLAR MARKET REGIONAL COMPANY SERVICES IN INCREASING THE INCOME OF NORTH KEPURAN MARKET TRADERS IN SURABAYA - Pramana, Bambang; Pratikto, Iqbal Surya (Investama : Jurnal Ekonomi dan Bisnis, 2025)
This research aims to analyze the role of the Surya Market Regional Company's services in increasing traders' income at Keputran Utara Market, Surabaya. The research focus includes implementing programs to increase traders' income through cleanliness, facilities, and market facilities and infrastructure. Factors such as capital, working hours, length of business, and number of traders were also taken into consideration in this research. The obstacles found included managing cleanliness, order and market infrastructure, which had an impact on the comfort of traders and visitors. This research uses a qualitative approach with interview methods, observation and document analysis related to the development of traditional markets in Surabaya. The research results show that although services such as security, parking facilities, prayer rooms and toilets are available, the Surya Market Regional Company has not been fully successful in managing the market to increase traders' income. These findings have implications for the management of traditional markets so they can compete with modern markets.